(untitled) (International Journal of Advanced Research in Science, Management and Technology, 2022)
Mobile phones have evolved into powerful image processing devices equipped with high-resolution cameras, color displays, and hardware-accelerated graphics. This survey paper describes a novel multimodal interactive image search system on mobile devices. The system, the Joint search with ImaGe, Speech, And Word Plus (JIGSAW ), takes full advantage of the multimodal input and natural user inter-actions of mobile devices. It is designed for users who already have pictures in their minds but have no precise descriptions or names to address them. By describing it using speech and then refining the recognized query by interactively composing a visual query using exemplary images, the user can easily find the desired images through a few natural multimodal interactions with his/her mobile device.